Impact of renin-angiotensin system inhibitors and beta-blockers on dental implant stability - Babak Saravi; Andreas Vollmer; Gernot Lang; Nicholai Adolphs; Zhen Li; Verena Giers; Peter Stoll (SpringerOpen, 2021)
Abstract Background Current experimental research suggests antihypertensive medication reduces the failure risk of dental implants due to enhanced bone remodeling. However, evidence from clinical studies evaluating the impact of antihypertensive medication on implant stability is lacking. Methods We retrospectively analyzed 377 implants in 196 patients (46 implants inserted in antihypertensive drug users (AH) and 331 implants in non-users (NAH)) for implant stability measured by radiofrequency analysis, and we determined the implant stability quotient (ISQ). AH subgroups were stratified by the use of beta-blockers, renin-angiotensin system (RAS) inhibitors, and both of the aforementioned. The impact of antihypertensive medication on ISQ values at implant insertion (primary stability) and implant exposure (secondary stability) was analyzed by a linear regression model with a regression coefficient and its 95% confidence interval (95% CI), adjusted for potential confounders. Results Time between implant insertion and implant exposure was 117.1 ± 56.6 days. ISQ values at insertion were 71.8 ± 8.7 for NAH and 74.1 ± 5.6 for AH, respectively. ISQ at exposure was 73.7 ± 8.1 for NAH and 75.7 ± 5.9 for AH. Regression analysis revealed that none of the AH subgroups were significantly related to ISQ at implant insertion. However, renin-angiotensin system inhibitors (RAS) were significantly associated with higher ISQ values at exposure (reg. coeff. 3.59, 95% CI 0.46-6.71 (p=0.025)). Conclusions Outcome of the present study indicates enhanced bone remodeling and osseointegration following dental implant insertion in patients taking RAS inhibitors than in non-users. Future randomized prospective studies must confirm these indicative results.